The COVID 19 Pandemic and the Fundamental Rights in the EU - Ana Maria Bolborici (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The year 2020 and also 2021 brought both progress and setbacks in terms of fundamental rights protection. The COVID-19 Pandemic triggered multiple crises not only at the sanitary level. In this context, people in Europe and also all over the world had the impress that their fundamental rights are not respected and limited. The paper offers a perspective about the impact of COVID-19 on human rights and emphasis some highlights weaknesses.